Gabapentin and Fluoxetine for treatment of psychological symptoms: a cross over study - Rahmanian, Mojgan; Ghorbani, Raheb (Archives of Advances in Biosciences, 2015)
The somatic and metabolic changes due to menopause can result in numerous symptoms including psychological symptoms. This study compares the effectiveness of Gabapentin vs. Fluoxetine in treatment of psychological symptoms of menopause. Methods:Eighty menopausal women with history of hot flashes and predefined psychological symptoms participated in a cross-over study conducted at the Amir-Al-Momenin hospital, Semnan, Iran. Participants were randomly divided into two groups: A and B. The study included two rounds of treatment, each 4 weeks long, separated by a two-week washout period. In the first round of treatment, group A was treated with Fluoxetine 20mg/d and group B with Gabapentin 300 mg/d. In the second round of treatment, group A received Gabapentin while group B received Fluoxetine (cross-over).All participants were asked to fill out the "Green Climacteric Scale" questionnaire at the beginning of the study and also following each round of treatment. They were also asked to monitor and keep track of the side effects of the medications by filling out another form. There was no significant difference between the two groups in age, body mass index, and age at menopause (p>0.05). The severity of irritability, fatigue, difficulty in concentrating, difficulty in sleeping, nervousness, and palpitation reduced to a significantly greater extent when the participants were treated with Gabapentin than when they were treated with Fluoxetine. Side effects (tremor) developed in only 2 Fluoxetine users and 2 Gabapentin users during the first 4 weeks of treatment. Our findings suggest that Gabapentin is more effective in alleviating the psychological symptoms of menopause than Fluoxetine. Thus, we recommend Gabapentin 300 mg/d for menopausal women who primarily complain about psychological symptoms, or those with contraindication to hormonal therapy.